PENGARUH DANA PIHAK KETIGA (DPK) DAN TINGKAT NON PERFORMING FINANCING (NPF) TERHADAP PEMBIAYAAN MURABAHAH PADA PT BANK SYARIAH MANDIRI (PERIODE 2010-2017) - Nurdiansyah, Dian Hakip; Mubarokah, isro'iyatul (Universitas Pendidikan Indonesia, 2020)
Function of Islamic Bank is financial institution that conduct business activities based on the principles of Islam Law, also operational activities by funds collecting from public in the form of savings, current accounts also deposits and will be disbursed by the bank to the public in the form of financing. The large funds raised by the bank it will increase financing disbursed.The size of the financing that disburse by Islamic bank would risk in result of non-payment financing has been granted. The high risk of financing disburse will be lower financing.The purpose of this research was to find out of Third Parties Fund, Non Performing Financing and Murabahah in PT Bank Syariah Mandiri and to analyze and explain The Influence of Third Parties Fund and Non Performing Financing, for both partially and simultaneously on Murabahah at PT Bank Syariah Mandiri. The research period is 2010-2017. While research method that use in this research is descriptive quantitative with data obtained from the quarterly financial statement of PT Bank Syariah Mandiri.The results showed that Third Parties Fund, Non Performing Financing and Murabahah continue to fluctuate. To partially test hypothesis showed that variable Third Parties Fund significant effect on Murabahah, while variable Non Performing Financing no significant effect on Murabahah. Simultaneously test show that Third Parties Fund and Non Performing Financing effect on Murabahah.